Tryptophan supplementation induces a positive bias in the processing of emotional material in healthy female volunteers. - Murphy, SE; Longhitano, C; Ayres, R; Cowen, P; Harmer, C (2006)
RATIONALE: The serotonin precursor L-tryptophan (TRP) is available as a nutritional supplement and is licensed as an antidepressant in a number of countries. However, evidence of its efficacy as the primary treatment for depression is limited, and the direct action of TRP on the symptoms of depression and anxiety has not been well-characterised. OBJECTIVES: The present study assessed whether TRP induces cognitive changes opposite to the negative biases found in depression and characteristic of those induced by serotonergic antidepressants in healthy volunteers. MATERIALS AND METHODS: Thirty eight healthy volunteers were randomised to receive 14 days double-blind intervention with TRP (1 g 3x a day) or placebo. On the final day, emotional processing was assessed using four tasks: facial expression recognition, emotion-potentiated startle, attentional probe and emotional categorisation and memory. RESULTS: TRP increased the recognition of happy facial expressions and decreased the recognition of disgusted facial expressions in female, but not male, volunteers. TRP also reduced attentional vigilance towards negative words and decreased baseline startle responsivity in the females. CONCLUSIONS: These findings provide evidence that TRP supplementation in women induces a positive bias in the processing of emotional material that is reminiscent of the actions of serotonergic antidepressants. This highlights a key role for serotonin in emotional processing and lends support to the use of TRP as a nutritional supplement in people with mild depression or for prevention in those at risk. Future studies are needed to clarify the effect of tryptophan on these measures in men.